Integrated gas dynamic and thermodynamic computational modeling of multicylinder 4-stroke spark ignition engine using gasoline as a fuel - Tirkey J.V.; Gupta H.N.; Shukla S.K. (My University, 2025)
This paper presents a computational tool for the evaluation of engine performance and exhaust emissions for four stroke multi-cylinder spark ignition engine which uses gasoline as a fuel. Gas dynamics flow in multi-cylinder intake and exhaust systems are modeled by using one-dimensional unsteady compressible flow equations. The hyperbolic partial differential equations are transferred into a set of ordinary differential equations by using method of characteristics and solved by finite difference method. Compatibility relationships between local fluid velocity and sonic velocity are expressed in terms of Riemann variables, which are constant along the position characteristics. The equations are solved numerically by using rectangular grid in the flow direction and time. In this model nitric oxide concentration is predicted by using the rate kinetic model in the power cycle and along the exhaust pipes. Carbon monoxide is computed under chemical equilibrium condition and then empirical adjustment is made for kinetic behaviors based upon experimental results. A good agreement is obtained in the comparison of computed and experimental results of instantaneous cylinder pressure, manifold pressure and temperature, and nitric oxide and carbon monoxide emissions level.